Characteristics of heavy ion beam-bombarded bacteria E. coli and induced direct DNA transfer - Phanchaisri B. (2014)
The goal of the work described here was to study ion beam interactions with bacteria and thus develop an understanding of the mechanisms involved in ion bombardment-induced direct gene transfer into bacterial cells. Ar ion beams at an energy of 26 keV and fluences ranging from 5 × 1014 to 4 × 1015 ions/cm2 were used to bombard bacterial cells of Escherichia coli strain DH5α. The bacteria were able to survive the low-temperature and low-pressure treatment conditions for at least a few hours. The ion bombardment created novel crater-like structures on the surface of the bacterial cell envelope, as observed by scanning electron microscopy. Four variously sized DNA plasmids carrying the ampicillin resistance gene were transferred and expressed in E. coli cells bombarded with ion fluences of 1 × 1015 and 2 × 1015 ions/cm2. The dependence of the DNA transfer on the plasmid DNA size, ion fluence and incubation time all suggests that the ion beam-induced surface crater-like structures provide the pathway for the mechanism that is responsible for the ion beam-induced DNA transfer. © 2002 Elsevier Science B.V. All rights reserved.